(untitled) (Economic and Political Thought, 2012)
The article analyzes the causes of the crisis in the German liberal party – Freie Democratische Partei (FDP). In the past, the party played an important role in the history of the Federal Republic of Germany and its representatives held the key political posts, e.g. Hans Dietrich Genscher. Since the 1990s, the FDP has been in crisis in spite of its success in the 2005 election to Bundestag. The author asks a question about the reasons of the crisis. The first of them he identifies is the actual lack of personalities such as Genscher and Graff Otto von Lambsdorff used to be. Another reason is a general crisis of parties in Germany; the FDP suffers from it in particular because it does not have a substantial group of a stable party electorate and so loses its supporters to other parties’ advantage. The FDP made an erroneous attempt to profile itself by postulating lower taxes. But in the unfavorable economic situation at the time and in coalition with Christian Democrats, it was unable to implement it and started to be perceived as a neoliberal party. With the increasing economic crisis, growing uncertainty of the society and people looking for support in the state and its benefits, the party started to be associated with the negative trends in the contemporary economy. In such an unfavorable constellation, the attempts to warm the party’s image and to show that it is not interested in gaining profits but in freedom in its broad sense have not been really effective.